2012
DOI: 10.1007/s12020-012-9699-7
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen synthesis genes CYP19A1, HSD3B1, and HSD3B2 in hypertensive disorders of pregnancy

Abstract: Hypertension in pregnancy is a multifactorial disorder caused by a complex combination of environmental factors and several predisposing genes. Since estrogen modulates placental vascular development, estrogen synthases are considered plausible candidate genes. The aim of this haplotype-based case-control study was to estimate whether polymorphisms of the maternal estrogen synthesis genes (CYP19A1, HSD3B1 and HSD3B2) are associated with preeclampsia (PE) and gestational hypertension (GH). To examine the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…8B). Importantly, placental aromatase deficiency has been found in women with preeclampsia (64), and a hCYP19A1 gene polymorphism associated with decreased aromatase levels has been reported to occur more commonly in preeclamptic patients (65). Notably, hGCM1, which we also found to be a target of miR-19b, was found to be markedly decreased in placentas of women with preeclampsia (66).…”
Section: Discussionmentioning
confidence: 55%
“…8B). Importantly, placental aromatase deficiency has been found in women with preeclampsia (64), and a hCYP19A1 gene polymorphism associated with decreased aromatase levels has been reported to occur more commonly in preeclamptic patients (65). Notably, hGCM1, which we also found to be a target of miR-19b, was found to be markedly decreased in placentas of women with preeclampsia (66).…”
Section: Discussionmentioning
confidence: 55%
“…Microarray analysis indicated a number of genes that were up- or down-regulated by the miR-518b mimic. Among the 124 target genes down-regulated more than 2-fold (Supplementary Table S1), two genes (tyrosine hydroxylase: TH and hydroxy-delta-5-steroid dehydrogenase, 3 beta- and steroid delta-isomerase 1: HSD3B1 ) were previously demonstrated to be involved in the pathogenesis of preeclampsia202122, and five genes (endothelin receptor type A: EDNRA , advanced glycosylation end product-specific receptor: AGER , wingless-type MMTV integration site family member 2: WNT2 , complement component 9: C9 , and transient receptor potential cation channel, subfamily M, member 2: TRPM2 ) play roles in preeclampsia with foetal growth restriction23242526272829303132 (Table 1). Likewise, among the 112 target genes up-regulated over 2-fold by the miR-518b mimic (Supplementary Table S2), four genes [hemopexin: HPX , serpin peptidase inhibitor, clade B (ovalbumin), member 2: SERPINB2 , lipoprotein, Lp(a): LPA , and tumour necrosis factor superfamily, member 10: TNFSF10 ] show involvement in preeclampsia35363738, and two genes (CD69 molecule: CD69 and stanniocalcin 1: STC1 ) are involved in preeclampsia with foetal growth restriction333439 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…miR-518b seems to control multiple target genes located on various chromosomes. Interestingly, some miR-518b target genes were previously demonstrated to associate with preeclampsia (e.g., TH and HSD3B1 for down-regulated genes, and HPX, SERPINB2, LPA and TNFSF10 for up-regulated genes)20212235363738 and with preeclampsia with foetal growth restriction (e.g., EDNRA, AGER, WNT2, C9 , and TRPM2 for down-regulated genes, and CD69 and STC1 for up-regulated genes)23242526272829303132333439. However, further experiments are needed to demonstrate a causal relationship between the expression of pregnancy-associated miRNAs and pregnancy-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid synthesis is catalyzed by several kinds of enzyme such as 3beta-hydroxysteroid dehydrogenase (HSD3B1 and HSD3B2), 21-hydroxylase (CYP21A2) and 11-hydroxylase (CYP11B1). In our latest investigation, we found that polymorphisms of HSD3B1 and HSD3B2 were not associated with PIH in the Japanese population [15]. In the Spanish population, it was also shown that CYP21A2 did not contribute to the risk for PIH [16].…”
Section: Discussionmentioning
confidence: 84%